(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
This article presents effects of group discussion on teaching & learning process of Ayurveda education. Discussion is a very important aspect of life to explore its dimensions and understanding. Study noticed group discussion support teaching & learning process significantly since it help to share knowledge, improve confidence level and explore student personality. The group discussion also supports introverted students to become familiar with their classmate. The investigation observed that most of students believe in the fact that group discussion as component of teaching lecture improves long lasting knowledge. The results of study suggested that teaching and learning process improved remarkably using group discussion as teaching component; the beneficial effect of group discussion attributed to the fact that it support students to become familiar with classmate, improve interactions between student and teacher, help to memorize studied material for long period of time, generate interest towards the study material, boost speaking skills and various aspect of a particular topic can be presented by group discussion since each and every one having own view for a specific topic. Group discussion improves efficiency of teaching and learning process since it involves participation of every student which might be not possible in conventional teaching. Article suggested that group discussion must be incorporated in teaching tool to explore education system of Ayurveda science.